Toque fisiogerontológico na doença de Alzheimer e a redução da apatia - Fortes, Rafael (2011)
From a humane approach, involving the touch in orthopedic physical therapy and respiratory diseases, the creation of a bond with the caregiver and given guidance as to the physical care and social on the patients with Alzheimer's at an advanced stage, it is possible to work with physical therapy under a look geriatric, encouraging the patient to control their thinking and behavioral changes, particularly apathy. This is a qualitative study using participant observation, interviews with caregivers, the Zarit Burden Interview, and a diary, where for three months, three patients with Alzheimer's disease at an advanced stage will undergo a physical therapy program. Every session will be accompanied by family caregivers, that will be instructed as to the environmental awareness, accessibility, physical care with the patient in addition to socialization and family integration. Creating, in this way, a new physical therapy approach aimed at improvement of behavioral changes in Alzheimer's disease at an advanced stage